Enhanced Gas Recovery with Carbon Dioxide Sequestration in a Water-drive Gas Condensate Reservoir: a Case Study in a Real Gas Field - Hossein Zangeneh; Mohammad Amin Safarzadeh (Journal of Petroleum Science and Technology, 2017)
Gas reservoirs usually have high recovery due to high mobility and low residual gas saturation, although some of them producing under water-drive mechanism have low recovery efficiency. Encroachment of water into these reservoirs traps considerable amount of gas and increases the maximum residual gas saturation, which results in the reduction of gas and condensate production. Generally, the recoveries of water-drive gas reservoirs vary between 35-75%, whereas depletion-drive reservoirs exhibit recoveries near 85%. In this work, a method was proposed for reducing water encroachment, sweeping reservoir gas content effectively, and enhancing the hydrocarbon recovery consequently. To this end, a condensate gas reservoir model, located in the south of Iran, was chosen to study the process. The injection was performed above the bottom-up aquifer from two horizontal wells, and the base gas was produced by four vertical wells. Three cases of inactive aquifer (Case I), active aquifer (Case II), and active aquifer with CO2 injection (Case III) were studied subsequently. The proposed gas-gas displacement method increases the recovery of reservoir especially the recovery of heavier components composing the main part of the condensate. Moreover, the injection of a huge volume of CO2 without significant CO2 production can be interesting from an environmental point of view and can be considered as a CO2 sequestration process.